2008
DOI: 10.1186/1471-2407-8-366
|View full text |Cite
|
Sign up to set email alerts
|

Dietary preference, physical activity, and cancer risk in men: national health insurance corporation study

Abstract: Background: The effects of vegetable preference and leisure-time physical activity (LPA) on cancer have been inconsistent. We examined the effects of dietary preference and physical activity, as well as their combined effect on cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 26 publications
3
75
1
3
Order By: Relevance
“…From 422 unique studies identified using the search strategy, 15 studies met the inclusion criteria (13)(14)(15)(16)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). One population-based case-control study by Campbell and colleagues, using the Canadian National Enhanced Cancer Surveillance Study, reported and analyzed data from Ontario and seven other Canadian provinces separately using different physical activity measurement modality, and hence, these were analyzed as two separate studies (25).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From 422 unique studies identified using the search strategy, 15 studies met the inclusion criteria (13)(14)(15)(16)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). One population-based case-control study by Campbell and colleagues, using the Canadian National Enhanced Cancer Surveillance Study, reported and analyzed data from Ontario and seven other Canadian provinces separately using different physical activity measurement modality, and hence, these were analyzed as two separate studies (25).…”
Section: Resultsmentioning
confidence: 99%
“…On restricting analysis to six high-quality studies (13,14,16,30,32,33), physical activity continued to have a significant inverse association with gastric cancer risk (OR ¼ 0.86; 95% CI, 0.75-0.99), with moderate heterogeneity (I 2 ¼ 51%, Cochran Q test P ¼ 0.07). After excluding two studies in which the control population was composed of patients with nongastric cancer, a stable association was persistent between physical activity and gastric cancer (14 studies; 0.78; 95% CI, 0.71-0.87; refs.…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 99%
See 3 more Smart Citations